Data on before and after the Traceability System of Veterinary Antimicrobial Prescriptions in Small Animals at the University Veterinary Teaching Hospital of Naples - Claudia Chirollo (Animals, 2021)
Over recent decades, antimicrobial resistance has been considered one of the most relevant issues of public health. The aim of our study was to evaluate the differences related to the prescription of antimicrobials at the University Veterinary Teaching Hospital, before and after the mandatory use of veterinary electronic prescription (VEP). In particular, the consumption of antimicrobials was examined, especially taking into consideration the recommendations of prudent use. A comparison of data collected before and after the use of electronic prescription highlighted that during the period chosen for the study, the choice of antimicrobial molecules was appropriate, favoring those of “first” and “second line.” However, prescription and the use of some molecules not registered for veterinary medicine were observed in the period before VEP. Broad-spectrum antimicrobials, including penicillins with β-lactamase inhibitors, as well as first-generation cephalosporins and fluoroquinolones, were the most frequently prescribed compounds. There are few studies conducted in Italy aimed at investigating the use of antimicrobials in companion animals under field conditions and with particular regard to prudent use recommendations. This type of study underlines the importance of electronic medical recording in veterinary practice and, above all, its usefulness in monitoring the use of certain antimicrobial agents classified as of critical importance in human medicine.